IMPROVING THE STUDENTS’ WRITING THROUGH TALKING STICK MODEL AT GRADE XI STUDENTS - Akmal Akmal; Chitra Latiffani (Smart Education, 2021)
This study aimed to improve the result learn student during and to study process makes writing simple sentence through talking stick model. And students’ responses toward the use of talking stick model in learning English writing. This model is expected to overcome the problem that occurs in the field. The methodology of research is classroom action research (CAR). The object of the research is students’ SMK Negeri 1 Pulau Rakyat, class XI2, that amount of 30 students, academic year of 2019/2020. The classroom action research in planning, the researcher used first cycle and the second cycle. Afterwards enter cycle that first pursuant to sequence use some step that is planning, acting, observing, reflecting and the second cycle of the same steps with the first cycle. In analyzing the data the researcher used descriptive quantitative. The result of analysis assess at the first cycle showing result that the mean score 66.8, in addition, there were 6 students passed KKM in cycle I, after percent 20%. And the second cycle showing result that mean score 86.0 in addition, there were 27 students passed KKM in cycle II, after percent 90%. In this research has KKM 75. The mentioned seen from efficacy indicator indicate that study process writing simple sentence through talking stick can mount result learn students, hence this research is expressed to succeed and discontinued at the second cycle, thereby can be expressed that improving the students’ writing simple sentence through talking model at grade XI students of SMK Negeri 1 Pulau Rakyat in academic year of 2019/2020, it is success